1996
DOI: 10.1007/bf02447128
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulating, antianemic, and adaptogenic effects of polysaccharides from plaster clover (Melilotus officinalis)

Abstract: Daily oral administration of polysaccharides extracted from plaster clover plants increased physical endurance (as determined in swimming tests) and body weight in mice and rats, stimulated the recovery of hematopoiesis in rats with experimentally produced lead anemia, and boosted the immune response to rat erythrocytes in mice, causing pronounced changes in the erythrocytic and leukocytic series and particularly in immunocompetent organs such as the thymus and spleen. Key Words: plaster clover; polysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Melilotus officinalis has been introduced as a component of a new drug by trade name of Semilil (Angipars). Previous studies have shown beneficial effects of Semilil such as improvement of blood circulation, reduction of inflammation, and improvement of lymphedema and immune system [ 12 , 13 ]. Results of clinical trials on Semilil indicated its safety and efficacy in human diabetic foot ulcer [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Melilotus officinalis has been introduced as a component of a new drug by trade name of Semilil (Angipars). Previous studies have shown beneficial effects of Semilil such as improvement of blood circulation, reduction of inflammation, and improvement of lymphedema and immune system [ 12 , 13 ]. Results of clinical trials on Semilil indicated its safety and efficacy in human diabetic foot ulcer [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its coumarinic extract was confirmed to have effect on lymphedema [7] and its polysaccharides had immunocorrecting, antianemia and adaptogenic effects [8]. However the anti-inflammatory effect on Melilotus suaveolens Ledeb had not been reported and related exploration on molecular biological mechanism of that plant on how to play an anti-inflammatory role remained limited.…”
Section: Discussionmentioning
confidence: 99%
“…In literatures, there were a few reports on Melilotus . It was documented that Melilotus is used to reduce spasm ( 2 ); its coumarinic extract have effects on lymphedema ( 3 ) and its polysaccharides have immunocorrecting, anti-anemia and adaptogenic effects ( 4 ). Although anti-inflammatory effect of M. officinalis was reported ( 5 ), exploration on M. suaveolens Ledeb on how to play an anti-inflammatory role at molecular level remained limited.…”
Section: Introductionmentioning
confidence: 99%